Structure and Rank of a Cyclic Code over a Class of Nonchain Rings - Nikita Jain; Sucheta Dutt; Ranjeet Sehmi (Journal of Mathematics)
The rings Z4+νZ4 have been classified into chain rings and nonchain rings based on the values of ν2∈Z4+νZ4. In this paper, the structure of a cyclic code of arbitrary length over the rings Z4+νZ4 for those values of ν2 for which these are nonchain rings has been established. A unique form of generators for a cyclic code over these rings has also been obtained. Furthermore, the rank and cardinality of a cyclic code over these rings have been established by finding a minimal spanning set for the code.